DO FLOODS LEAVE LASTING SCARS? LONG-TERM EFFECT OF FLOOD EVENTS ON INDONESIA'S REGIONAL ECONOMY - Amesta Kartika Ramadhani; Sephia Dwi Astuti; Ashtian Ultanti; Anggi Rahajeng; Fatima Putri Prativi (Journal of Applied Economics in Developing Countries, 2026)
As climate-related disasters increase in intensity and frequency, Indonesia is becoming more vulnerable to their impacts. Among these disasters, flooding is one of the most threatening hazards, causing both short and long-term economic consequences. While existing literature reports the impact of a single event, the impact of disaster on economic performance or immediate impact of disaster, the dynamic impacts on both GRDP per capita and inequality remain underexplored. To address this research gap, this study analyzes the economic impacts of floods using a Panel Autoregressive Distributed Lag (P-ARDL) model. It examines how floods affect GRDP per capita and inequality levels in both short and long run. The analysis also incorporates other explanatory variables, including Foreign Direct Investment (FDI), Domestic Investment (DDI), the Human Development Index (HDI), and population size.  The results indicate that, in the long run, floods have a negative effect on GRDP per capita; a 1% increase in flood events reduces GRDP per capita by 0.48%. In the short term, every 1% increase in flood frequency is associated with a 0.013% reduction in per capita GRDP. This study also reveals that floods have a significant negative impact on income inequality in both the short and long term. However, this paradoxical finding needs careful interpretation. It may not indicate an increase in social welfare but rather reflects the impact of flooding on wealthier groups, potentially narrowing the gap. Further research is needed to confirm this. This research underscores the importance of improving flood mitigation to maximize flood prevention and strengthen the resilience of economic productivity. Furthermore, the research findings need to be further explored, including the mechanisms by which floods reduce per capita GRDP and explore how floods can reduce inequality.